2021
DOI: 10.11002/kjfp.2021.28.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Tunisian plants extracts on oxidative stress and lipid accumulation in HepG2 cells

Abstract: hydrogen peroxide(H 2 O 2 ), hydroxyl ion(OH -) 및 singlet oxygen( 1 O 2 ) 등으로부터 세포를 보호하고, 여러 질병을 예방하기 위한 식 물 유래 천연 항산화제를 통한 체내 항산화 방어 시스템 향상 이 필요하다(Lam 등, 2020).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…On the other hand, Kratchanova et al (2010) [81] reported a higher ORAC value of 170 µmol TE g −1 for a water extract with the total phenolic content of 17.66 mg GAE g −1 , which is lower than in our study. Moreover, Kim and Kim (2021) [82] and Dudonne et al ( 2009) [83] reported significantly higher ORAC values of 2600 µmol TE g −1 in DMSO extract and 2963 µmol TE g −1 in a water extract, with total phenolic contents similar to those in our study, 44.07 and 59.85 mg GAE g −1 , respectively. There are several explanations for the discrepancies between the total phenolic contents, which were shown to correlate with the antioxidant capacity in Laurus nobilis L. leaf extracts [30,81], and the reported ORAC values.…”
Section: Antioxidant Capacitysupporting
confidence: 88%
“…On the other hand, Kratchanova et al (2010) [81] reported a higher ORAC value of 170 µmol TE g −1 for a water extract with the total phenolic content of 17.66 mg GAE g −1 , which is lower than in our study. Moreover, Kim and Kim (2021) [82] and Dudonne et al ( 2009) [83] reported significantly higher ORAC values of 2600 µmol TE g −1 in DMSO extract and 2963 µmol TE g −1 in a water extract, with total phenolic contents similar to those in our study, 44.07 and 59.85 mg GAE g −1 , respectively. There are several explanations for the discrepancies between the total phenolic contents, which were shown to correlate with the antioxidant capacity in Laurus nobilis L. leaf extracts [30,81], and the reported ORAC values.…”
Section: Antioxidant Capacitysupporting
confidence: 88%
“…For quantification, the standard curve using gallic acid equivalent was constructed. TFC was measured using the method described by Kim et al (2021). To 20 μL of each sample treated with a browning inhibitor, 200 μL of diethylene glycol and 20 μL of 1 N NaOH were added.…”
Section: Determination Of Total Polyphenol (Tpc) and Total Flavonoid ...mentioning
confidence: 99%
“…The FRAP of the processed fruits was significantly higher than that of the original fruit at the tap water immersion, slicing, and 1% AA treatment steps; however, no significant differences were observed after the drying step (p<0.05). Polyphenols exhibit various types of bioactivities, including reactive oxygen species removal; furthermore, the bioactivities of flavonoids, secondary metabolites with a polyphenol structure, include anticancer and anti-inflammatory effects (Kim and Kim, 2021). At the 100 ppm NaClO treatment step, the TPC and TFC of Fuji apples were distinctly lower than those of the original fruit.…”
Section: Evaluation Of Antioxidant Activitiesmentioning
confidence: 99%